Indonesia's 2023 MIKTA Chairmanship as A Middle Power Foreign Policy: Advancing Multilateralism From A Like- Minded Partnership Standpoint - Ifdal, Abdurrahman Al-Fatih (Kementerian Luar Negeri Republik Indonesia, 2023)
A sphere of multilateralism is often construed as a prerequisite for a like-minded middle power partnership. It reflects the very nature of middle power partnerships. This paper seeks to explore Indonesia’s middle power foreign policy in advancing multilateralism through its MIKTA (Mexico, Indonesia, South Korea, Turkey, and Australia) chairmanship in 2023. This paper thus collects relevant data from MIKTA’s resources and documents to further scrutinize its middle power agenda. It should be noted that MIKTA’s flexibility in organizing its agenda is an indispensable part of itself. Thus, this paper provides in-depth research on geopolitical trends of a middle powers partnership that is like-minded in nature. It then concludes how such trends influence Indonesia’s chairmanship in MIKTA. This paper is structured to understand and interpret Indonesia’s 2023 MIKTA chairmanship from the perspective of like-mindedness in foreign policy analysis. For such, the paper will use a foreign policy action analysis with a primary focus on actions conducted by and/or in relation to MIKTA. This paper shows that Indonesia’s 2023 chairmanship in MIKTA is a quest to demonstrate Indonesia’s middle power foreign policy. This paper recommends for Indonesia’s 2023 MIKTA chairmanship to critically transform MIKTA’s minilateralism approach in order to produce concrete deliverables by starting to utilize multilateralism as a means to fulfill Indonesia’s interests as a middle power and MIKTA’s institutional purposes as a norm- builder in addressing major global issues.